2015
DOI: 10.3310/hta19500
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility randomised controlled trial of a motivational interviewing-based intervention for weight loss maintenance in adults

Abstract: This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (www.publicationethics.org/).Editorial contact: nihredit@southampton.ac.ukThe full HTA archive is freely available to view online at www.journalslibrary.nihr.ac.uk/hta. Print-on-demand copies can be purchased from the report pages of the NIHR Journals Library website: www.journalslibrary.nihr.ac.uk Criteria for inclusion in the Health Technology Assessment journalReports are published in Health Technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 194 publications
1
56
0
3
Order By: Relevance
“… 23 Given the importance of motivation and support, a very recent feasibility trial of motivational interviewing showed that face-to-face and phone interviews improved retention in the study, and increased weight maintenance (−2.8 kg vs the control group). 27 All these studies confirm that the extended care approach, with monthly or more frequent contacts, in person or via telephone or Internet, can improve successful weight loss. They also reduce the risk of weight regain during the maintenance phase, with the exception of eHealth interventions, where evidence for effectiveness is limited 28 and was not confirmed in a meta-analysis.…”
Section: Strategies To Promote Weight Loss Maintenancementioning
confidence: 64%
“… 23 Given the importance of motivation and support, a very recent feasibility trial of motivational interviewing showed that face-to-face and phone interviews improved retention in the study, and increased weight maintenance (−2.8 kg vs the control group). 27 All these studies confirm that the extended care approach, with monthly or more frequent contacts, in person or via telephone or Internet, can improve successful weight loss. They also reduce the risk of weight regain during the maintenance phase, with the exception of eHealth interventions, where evidence for effectiveness is limited 28 and was not confirmed in a meta-analysis.…”
Section: Strategies To Promote Weight Loss Maintenancementioning
confidence: 64%
“…16 This strategy is the basis to achieve a significant adherence to the program 36 and has been successfully incorporated into behavioral programs aimed at healthy diet and habitual physical activity for weight loss in several diseases. [37][38][39][40] Patients were provided the user-id and password to access the system following a structured face-to-face meeting, and motivation to change was tested by appropriate, validated tests. 14 Reinforcements were provided during follow-up visits, in a similar way irrespective of treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…The first group achieved a mean loss of BMI 1 kg/m 2 lower than the control group with 95% confidence interval Cl -2.2 kg/m 2 to 0.2 kg/m 2 and the average difference in loss of weight was 2.8 kg with 95% Cl -6.1 kg to 0.5 kg. The obtained results suggest that intensive intervention with MI would support long-term weight loss [21].…”
Section: Motivational Interviewing Application In Obesity Reduction -mentioning
confidence: 70%